Introduction - Benjamin Burlingham (Journal of Teaching and Learning with Technology)
Recent advances in the science of teaching and learning have opened the eyes of many instructors to course design, instructional practice, and assessment techniques intended to enhance and individualize student educational experience. Achieving these goals is difficult enough in a class of 20 students, but these challenges are only magnified in large-enrollment courses comprising anywhere between 100 students in a classroom to numerous sections of 500+. Instructors of large-enrollment classes share a common concern: How can one person provide engaging learning opportunities and assessments to meet the unique needs of each student when faced with a sea of faces in the classroom? Considering these overwhelming challenges, some instructors are asking, “Is the use of technology in the classroom the solution?”